IMPLEMENTASI METODE KETELADANAN RASULULLAH DALAM KURIKULUM PENDIDIKAN AGAMA ISLAM TELAAH PEMIKIRAN ABDUL FATTAH ABU GHUDDAH - Abbas, Ngatmin; Rochmawan, Alfian Eko; Fathurrohman, Mukhlis; Ulfah, Yetty Faridatul (MAMBA'UL 'ULUM, 2024)
This research delves into the implementation of the method of emulating Prophet Muhammad (peace be upon him) within the Islamic religious education curriculum using a literature-based approach. The book "Rasulullah Sang Guru" authored by Abdul Fattah Abu Ghuddah serves as the primary source material for this study. The primary objective of the research is to evaluate the relevance of employing the method of emulating the Prophet in the context of Islamic religious education in Indonesia. The research findings indicate that although the method of emulating the Prophet is not fully integrated into classroom instruction, Islamic religious education instructors consistently demonstrate these principles in their daily lives outside the classroom, such as adhering to Islamic dress codes and exhibiting religious behavior. The implication of this research emphasizes the importance of developing Islamic religious education curricula that place a stronger emphasis on the practical application of the Prophet's method of emulation. Collaboration among academics, practitioners, and policymakers is required to develop curricula that are more effective and relevant. This research underscores that the method of emulating Prophet Muhammad holds significant value in Islamic education. The use of "Rasulullah Sang Guru" provides a deeper understanding of the method of emulating Prophet Muhammad.